Evaluation of Oxidative Stress in Blood of Domestic Chickens and Eurasian Magpies (Pica pica) - Iemmi, Tiziano; Menozzi, Alessandro; Basini, Giuseppina; Grasselli, Francesca; Grolli, Stefano; Ramoni, Roberto; Serventi, Paolo; Quintavalla, Fausto; Bertini, Simone (Journal of avian medicine and surgery, 2021)
A physiological equilibrium exists between pro- and antioxidant factors. When the oxidant factors exceed the capacity of their removal or inactivation, oxidative stress (OS) occurs. The OS levels were assayed in plasma obtained from 2 bird species. Blood samples were collected from 20 healthy domestic chicken hens, 10 living in an intensive farming environment and 10 free-range, and from 18 healthy Eurasian magpies (Pica pica; 7 females and 11 males, with an estimated age of >1 year of age). For OS biomarker assessment, the determinable reactive oxygen metabolites (d-ROMs) were measured, and the plasmatic antioxidant test (PAT) was performed; the OS index (OSI) was then calculated (d-ROMs/PAT × 1000) as a parameter of overall oxidative stress. Moreover, lipid peroxidation was assessed by measuring plasmatic malondialdehyde (MDA) levels. A hematological evaluation was also performed on each bird with a hemocytometer, on which a blood sample was placed to obtain both a total and differential white blood cell (WBC) count. In hens, OSI and MDA levels were significantly higher (P = .04, and P = .004) in subjects from intensive farming (14.7 ± 7.1 and 27.2 ± 10.4 nmol/mL) than in those bred in rural conditions (5.6 ± 10.3 and 8.2 ± 13.3 nmol/mL). In magpies, a positive correlation between the total WBC count and OS was found, and both d-ROMs and OSI were significantly higher (P = .03) in subjects with a total WBC count greater than the median value (20.4 × 103 cells/µL) with respect to those with a total WBC count less than the median value. The results generated from this study indicate that higher OS levels occurred in hens bred in an intensive indoor farm environment compared with outdoor free-range conditions. Possibly the higher OS levels could be related to the higher stocking density and dust levels found in the indoor facility. Additionally, the correlation between OS biomarker levels in magpies and total WBC count suggests that OS level is influenced by immune response, in agreement with previous studies. Collectively, present data seem to be promising for the application of OS measurement in avian medicine for health and animal welfare monitoring.